Parasitoides pupais de Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) no município de Mossoró/RN - Silva, Barbara Karine de Albuquerque (Universidade Federal Rural do Semi-Árido, 2017)
The production and export of tropical fruits in nature is one of the main agricultural activities of the Northeastern Brazilian region, which is characterized by the semiarid climate. However, the presence of pest insects, such as fruit flies, hampers the production and export in this fruit segment. The main species of fruit flies of economic and quarantine importance in Brazilian semiarid is Ceratitis capitata (Wiedemann) (Diptera: Tephritidae). The use of synthetic insecticides is still the most usual method for suppression of these populations. However, in the context of integrated production, the use of beneficial organisms is a desirable practice for a population decrease of these tefritídeos, featured the parasitoids. Although there is some information about the larval parasitoids of fruit flies in the semi-arid, there are practically no records of the occurrence of pupal parasitoids of C. capitata, in mentioned region. Therefore, the objective of this work was to verify if there are pupal parasitoids associated to C. capitata in the Brazilian semiarid. The survey was carried out in the municipality of Mossoró (RN), from May to September 2016. To obtain the parasitoids, pupae of C. capitata produced in the laboratory were exposed to natural parasitism in the field. In the surveys, four species of parasitoids were obtained, all belonging to the order Hymenoptera and family Pteromalidae: Spalangia simplex Perkins; Spalangia leiopleura Gibson; Spalangia impunctata Howard; and Pachycrepoideus vindemmiae (Rondani), the latter being the most common species, with a natural parasitism index of 12.17%. These are the first reports of S. leiopleura and S. impunctata parasitizing pupae of C. capitata, in Brazil
Pupal parasitoids of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) in the municipality of Mossoró/RN
Keywords: Mosca-do-mediterrâneo; Produção Integrada; Controle biológico; Pteromalídeos; Mediterranean Fruit Fly; Integrated production; Biological Control; Pteromalids; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA